Rise and dissemination of aminoglycoside resistance: the aac(6′)-Ib paradigm - Ramirez, María Soledad; Nikolaidis, Nikolas; Tolmasky, Marcelo (Frontiers in Microbiology, 2013)
Enzymatic modification is a prevalent mechanism by which bacteria defeat the action of antibiotics. Aminoglycosides are often inactivated by aminoglycoside modifying enzymes encoded by genes present in the chromosome, plasmids, and other genetic elements. The AAC(6’)-Ib (aminoglycoside 6’-N-acetyltransferase type Ib) is an enzyme of clinical importance found in a wide variety of gram-negative pathogens. The AAC(6’)-Ib enzyme is of interest not only because of his ubiquity but also because of other characteristics, it presents significant microheterogeneity at the N-termini and the aac(6’)-Ib gene is often present in integrons, transposons, plasmids, genomic islands, and other genetic structures. Excluding the highly heterogeneous N-termini, there are 45 non-identical AAC(6’)-Ib related entries in the NCBI database, 32 of which have identical name in spite of not having identical amino acid sequence. While some variants conserved similar properties, others show dramatic differences in specificity, including the case of AAC(6’)-Ib-cr that mediates acetylation of ciprofloxacin representing a rare case where a resistance enzyme acquires the ability to utilize an antibiotic of a different class as substrate. Efforts to utilize antisense technologies to turn off expression of the gene or to identify enzymatic inhibitors to induce phenotypic conversion to susceptibility are under way.